1971
DOI: 10.1002/anie.197101051
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ligands on the Activity and Specificity of Soluble Transition Metal Catalysts

Abstract: The reaction of a covalently a-bonded Iigand (alkyl group, hydrogen)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(19 citation statements)
references
References 50 publications
3
16
0
Order By: Relevance
“…This result indicates that the activity of CGMs decreases with an increasing net charge on the central atom. This supports Olive's idea [35] that the stronger the electron donating ability of a ligand connected to the central metal atom of the catalyst is, the less the net charge on the metal atom, and the higher the activity of the polymerization are. It appears that the activity does not evenly respond to the amount of the net charge.…”
Section: Qeq Charge and Activity Of Cgmsupporting
confidence: 77%
See 2 more Smart Citations
“…This result indicates that the activity of CGMs decreases with an increasing net charge on the central atom. This supports Olive's idea [35] that the stronger the electron donating ability of a ligand connected to the central metal atom of the catalyst is, the less the net charge on the metal atom, and the higher the activity of the polymerization are. It appears that the activity does not evenly respond to the amount of the net charge.…”
Section: Qeq Charge and Activity Of Cgmsupporting
confidence: 77%
“…[35] It was pointed out that there are four factors which are most important in terms of affecting the catalyst performance: the transition metal-olefin interaction, the metal-alkyl bond stability, the influence of other ligands and substituents attached to the rings, and the steric effect. If the ligand is a good electron donor, it will reduce the positive charge on the metal and thus weaken the bonding between the metal and other ligands, particularly the unstable M-R bond, which will become more reactive.…”
Section: Qeq Charge and Activity Of Cgmmentioning
confidence: 99%
See 1 more Smart Citation
“…A polymerization mechanism, which avoids the ion pair separation, was proposed by Olivé et al [38] as early as 1970 assuming olefin coordination to a bimetallic Cp 2 TiCH 3 d+ Al(CH 3 ) 2 Cl 2 d-adduct. Hoffmann [39] confirmed this situation if a pentacoordinated Ti atom is assumed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Olivé [10] concluded that there are four factors affecting the catalyst activity the most: the transition metal-olefin interaction, the metal-alkyl bond stability, the influence of other ligands and substituents attached to the rings, and the steric effect. By studying the influence of central metal atom charge and steric effect on catalytic activity of Zr-based metallocenes, Möhring and Coville [11] pointed out that the electronic effect can contribute as much as 80% of the change in polymerization activity.…”
Section: Introductionmentioning
confidence: 99%